Comparative Study of Safety and Efficacy between Propofol-Fentanyl Versus Propofol-Dexmeditomidine Combination For Sedation in Upper Gastro-Intestinal (GI) Endoscopic Procedures- A Prospective Randomised Study - Basarigidad, Ajay; Killedar, Sandeep (Academia Anesthesiologica International, 2019)
Background: Endoscopy in patients with gastrointestinal disorders (GI) is of immense benefit for diagnostic and therapeutic measures. Inspite of use of flexible fibreoptic equipments, endoscopy remains an unpleasant experience for most patients. The purpose of sedation in these patients is to relieve anxiety, discomfort or pain, and diminish memory of the event.[1] There has been a general consensus that moderate sedation provides adequate control of pain and anxiety during endoscopic procedures. Conscious sedation enables patients to maintain their response to verbal and tactile stimuli without losing cardiovascular and ventilatory function.[2] The aim of study is to compare the safety and efficacy between propofol-fentanyl and propofol-dexmeditomidine combination for sedation in upper gastro-intestinal (GI) endoscopic procedures. Subjects and Methods: A prospective study of 70 cases of both sexes belonging to ASA Grade I,II and III. Planed for elective upper GI endoscopies under sedation were included in this study were randomly selected. The study group was divided in two groups of 35 each, Group A Propofol-Fentanyl (PF) and Group (B) Propofol-Dexmeditomedine (PD). In the PF group, patient was administered fentanyl 2mcg/kg initially followed by Propofol loading dose of 1.5mg/kg over five minutes. Then propofol infusion was started at 50mcg/kg/min to achieve bis value 50-60. Then endoscopy was done. If the subject did not tolerate the endoscope or patient experienced pain during the entire procedure then additional propofol bolus of 0.3 mg/kg was given. Similarly in PD group, the subject was given 1mcg/kg dexmeditomidine instead of Fentanyl, rest the same. Meanwhile HR, BIS value, SPO2, MAP were noted. Results: It was found that there was significant difference in SpO2 Heart rate,,Mean, BIS Meanwhile 54.3% of patients required airway manoeuvre to maintain Saturation in PF group while only 2.9% patients of PD group required airway support. This difference in airway manoeuvre was statistically significant. Conclusion: we concluded that propofol dexmeditomidine group had better respiratory parameters, better hemodynamic stability, lesser need of total propofol. Propofol dexmeditomidine had better satisfaction levels among patients as compared to propofol fentanyl group butrecovery time of Propofol-fentanyl group was faster than propofol dexmeditomidine group.Except for time taken for recovery, PD group was both safer and more efficacious. Overall Propofol Dexmeditomidine group achieved better conditions for sedation in upper GI endoscopy than Propofol-Fentanyl.